Political Economy of Public Policies: Insights from Distortions to Agricultural and Food Markets - Kym Anderson; Gordon Rausser; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
The agricultural and food sector is an ideal case for investigating the political economy of public policies. Many of the policy developments in this sector since the 1950s have been sudden and transfirmational, while others have been gradual but persistent. This article reviews and synthesizes the literature on trends and fluctuations in market distortions and the political-economy explanations that have been advanced. Based on a rich global data set covering a half-century of evidence on commodities, countries, and policy instruments, we identify hypotheses that have been explored in the literature on the extent of market distortions and the conditions under which refirm may be feasible.
Keywords: D72; D78; F13; F14; N50; Q17; Q18; 330; Agrarpolitik; Ernährungspolitik; Agrarmarkt; Nahrungsmittelmarkt; Regulierung; Public Choice; Staatsversagen; Welt